An Analysis of Reading Comprehension by Using Descriptive Text at the Eleventh-Grade Students of SMA N 9 Jambi - Nurhidayati, Fadia; Suyadi, Suyadi; Aisyah, Siti (Universitas Batanghari Jambi, 2024)
This research aims to determine students' reading comprehension by using descriptive text. This research uses descriptive quantitative. The research instrument in this research used a test. The test consists of 20 multiple-choice questions, there are two different descriptive texts with 10 questions in each descriptive text. The data for this research are class XI students at SMA N 9 Jambi with a total of 36 students. In this research, data collection uses a test that functions to determine students' reading comprehension, data collection includes the following: the researcher gives a test in the form of 20 multiple choice questions, there are two different descriptive texts with 1 text each for 10 questions, then the researcher ask students to read and understand the text in depth after that student are given 90 minutes to answer the questions. Data analysis uses analysis of students' reading comprehension using descriptive text. These results indicate that students' reading comprehension using descriptive text in class XI F 2 is in the “High’ category. The results show the mean score of the students’ reading comprehension of descriptive text is 83,5%. That is 29 students (81%) obtained the “High” category with a score range of 70-100. The highest score was 100 and the lowest score was 25. Most of them in the